Comparative genomic insights into habitat adaptation of coral-associated Prosthecochloris - Nie, Zhaolong; Tang, Kaihao; Wang, Weiquan; Wang, Pengxia; Guo, Yunxue; Wang, Yan; Kao, Shuh-Ji; Yin, Jianping; Wang, Xiaoxue (Frontiers in Microbiology, 2023)
Green sulfur bacteria (GSB) are a distinct group of anoxygenic phototrophic bacteria that are found in many ecological niches. Prosthecochloris, a marine representative genus of GSB, was found to be dominant in some coral skeletons. However, how coral-associated Prosthecochloris (CAP) adapts to diurnal changing microenvironments in coral skeletons is still poorly understood. In this study, three Prosthecochloris genomes were obtained through enrichment culture from the skeleton of the stony coral Galaxea fascicularis. These divergent three genomes belonged to Prosthecochloris marina and two genomes were circular. Comparative genomic analysis showed that between the CAP and non-CAP clades, CAP genomes possess specialized metabolic capacities (CO oxidation, CO2 hydration and sulfur oxidation), gas vesicles (vertical migration in coral skeletons), and cbb3-type cytochrome c oxidases (oxygen tolerance and gene regulation) to adapt to the microenvironments of coral skeletons. Within the CAP clade, variable polysaccharide synthesis gene clusters and phage defense systems may endow bacteria with differential cell surface structures and phage susceptibility, driving strain-level evolution. Furthermore, mobile genetic elements (MGEs) or evidence of horizontal gene transfer (HGT) were found in most of the genomic loci containing the above genes, suggesting that MGEs play an important role in the evolutionary diversification between CAP and non-CAP strains and within CAP clade strains. Our results provide insight into the adaptive strategy and population evolution of endolithic Prosthecochloris strains in coral skeletons.